Inventarisasi Kerusakan Jalan SDN 04 Damon Bengkalis Dengan Metode PCI Menggunakan ArcGIS 10.8 - Saputra, Yogi Andri; Saputra, Hendra (Politeknik Negeri Bengkalis, 2024)
This study applies the Pavement Condition Index (PCI) method integrated with ArcGIS 10.8 for Road Damage Data Inventory in SDN 04 Damon, Bengkalis District. This research aims to identify and analyze road conditions around the school, with a focus on road segments that receive a